Adaptive consensus tracking control of non-affine non-linear MASs based on Taylor decoupling technology and an event-triggered design strategy - Wang, Li; Liu, Chaoda; Shang, Zihao (Frontiers in Physics, 2023)
This paper studies the consensus tracking control problem for a class of uncertain nonaffine nonlinear multi-agent systems(MASs). Firstly, different from the separation design scheme using the mean value theorem in the previous works, this paper not only uses the mean value theorem, but also introduces the Taylor decoupling method to decouple the complex unknown nonaffine structure. Secondly, in order to solve the difficulty of unknown nonlinear functions in the nonlinear MASs, an intelligent technique based on neural networks is used in this paper. In addition, compared with the existing traditional event-triggered control strategy based on relative threshold, an improved event-triggered control strategy based on the decreasing function of error variables is introduced to reduce the waste of unnecessary resources. The theoretical result shows that the whole closed-loop system is stable under the action of the proposed control protocol. Finally, the simulation experiment verifies the effectiveness of our control method.